THE COMMUNITY BASED TOURISM MANAGEMENT OF BANSUANKLUAI, BANSONG SUB, WIENGSA, SURATTHANI PROVINCE - Khaykhaw , Prapai; Bunkumnerd , Sanai; Sutaim , Pamornrat (Journal of MCU Nakhondhat, 2021)
The objectives of the research article were: 1) study the context of tourism management condition of Bansuankluai, Bansong sub, Wiengsa, Suratthani Province, and 2) study tourism management of Bansuankluai community, Bansong sub distract, Wiengsa distract, Surat Thani province. This study was qualitative research, information from the document, in depth interview and focus group discussion, to select a specific sample. Person who is directly involved and plays a role in the management of community tourism. Key informants such as 4 groups: 1) community committees, 2) people, 3) government agencies, and 4) entrepreneurs and stakeholders.for all 16 persons by using data analysis and overview summary. The finding indicates that 1. Management context such as 1.1) Area, use resources for maximum benefit and develop into a natural tourist attraction with unique local characteristics, 1.2) Resource base Use the community rights process to participate in the management, maintenance and sustainable use, 1.3) Management, applying rules, regulations and rules for sharing the resource base in the community, 1.4) Process and Activities Integration as a tourist attraction that reflects the identity and identity of local resources. to build a strong foundation for the community, and 1.5) Community organization There is a distribution of work roles, dividing work to do in the form of community committees. And 2. Sustainable management: 2.1) tourism potential Support tourists and management focuses on preserving resources and the environment rather than focusing on economic benefits, 2.2) Sustainable thought process Ecotourism forms and activities are bridges between communities and tourists, exchanging knowledge of lifestyles and cultures, 2.3) network, participation, promotion, support, and mentoring of tourism management using mechanisms for communication, exchange and experience, and 2.4) community leaders are leaders of change. Inspire followers to achieve what they desire.